Can we still believe the Bible? : an evangelical engagement with contemporary questions - Blomberg, Craig (2014)
"Challenges to the reliability of Scripture are perennial and have frequently been addressed. However, some of these challenges are noticeably more common today, and the topic is currently of particular interest among evangelicals. ... Blomberg offers an accessible and nuanced argument for the Bible's reliability in response to the extreme views about Scripture and its authority articulated by both sides of the debate. He believes that a careful analysis of the relevant evidence shows we have reason to be more confident in the Bible than ever before. As he traces his own academic and spiritual journey, Blomberg sketches out the case for confidence in the Bible in spite of various challenges to the trustworthiness of Scripture, offering a positive, informed, and defensible approach."--Publisher description.
Aren't the copies of the Bible hopelessly corrupt? -- Wasn't the selection of books for the canon just political? -- Can we trust any of our translations of the Bible? -- Don't these issues rule out biblical inerrancy? -- Aren't several narrative genres of the Bible unhistorical? -- Don't all the miracles make the Bible mythical?
Includes bibliographical references (pages 227-274) and indexes.
Keywords: Bible -- Evidences, authority, etc